2005
DOI: 10.2174/1389557053175362
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antitumor Agents: Marine Sponge Alkaloids, their Synthetic Analogs and Derivatives

Abstract: Present review describes research on novel natural antitumor agents isolated from marine sponges. More than 90 novel cytotoxic antitumor compounds and their synthetic analogs have shown confirmed activity in vitro tumor cell lines bioassay and are of current interest to NCI for further in vivo evaluation. A great problem, to use directly the reservoir of marine organisms for therapy is the very low availability and the isolation of only very small amounts of the biologically active substances from the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(48 citation statements)
references
References 70 publications
1
47
0
Order By: Relevance
“…In this regard, DAMN, acetone, and cyclohexyl isocyanide were stirred in the presence of guanidinium-based sulfonic acid as an acidic organocatalyst in water to lead to the synthesis of 5-(cyclohexylamino)-1,6-dihydro-6,6-dimethylpyrazine-2,3-dicarbonitrile 6a in 90 % yield. As indicated in Table 2 (entries [13][14][15][16][17], to evaluate the use of this approach, a variety of aliphatic and aromatic ketones and various isocyanides with DAMN were condensed under similar circumstances. The reactions proceeded very cleanly, and no undesirable side reactions were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, DAMN, acetone, and cyclohexyl isocyanide were stirred in the presence of guanidinium-based sulfonic acid as an acidic organocatalyst in water to lead to the synthesis of 5-(cyclohexylamino)-1,6-dihydro-6,6-dimethylpyrazine-2,3-dicarbonitrile 6a in 90 % yield. As indicated in Table 2 (entries [13][14][15][16][17], to evaluate the use of this approach, a variety of aliphatic and aromatic ketones and various isocyanides with DAMN were condensed under similar circumstances. The reactions proceeded very cleanly, and no undesirable side reactions were observed.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the synthetic potentialities of MCRs with SO 3 H-functionalized BrĂžnsted acid as environmentally benign and a recyclable catalyst have been combined to prepare quinoxalines [16] and pyrazines [17][18][19][20][21][22], which are seen in some important marketed drugs (I-III) [23][24][25], and urazole derivatives which also exhibit biological activities (IV-VII) [26][27][28][29] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of PASS to phytoconstituents has been exhibited in earlier investigations [12][13][14]. The current version of PASS is capable of predicting over 3750 biological effects, biochemical modes of action, specific toxicities, and metabolic terms based on 2D structures or canonical simplified molecular-input line-entry system (SMILES) with a mean accuracy of almost 95%.…”
Section: Introductionmentioning
confidence: 99%
“…Marine sponges are incredible source of novel pharmacologically active compounds (Thomas et al, 2010) which have earlier shown potent efficacy against various diseases. They are known to possess diverse pharmacological activity in several diseases such as cancer, neurodegeneration, type-2-diabetes, fungal and microbial infections (Bhosale et al, 1999;Dembitsky et al, 2005;Rao et al, 2006;Coello et al, 2009;GuzmĂĄn et al, 2011;Takei et al, 2010). These biological activities have been attributed to the presence of novel sterols, metabolites including steroids, terpenoids, alkaloids, cyclic peptides and unsaturated fatty acids (Litchfield et al, 1976;Findlay and Patil, 1985;Elenkov et al, 1999).…”
Section: Introductionmentioning
confidence: 99%